Misappropriation and dilution of indigenous people’s cultural expression through the sales of their arts and crafts: should more be done? - Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Abd. Jalil, Juriah; Hamzah, Hamimah; Daud, Mahyuddin (Universiti Putra Malaysia Press, 2015)
Indigenous cultural expressions, a component of traditional cultural expressions (TCEs), are drawing tourists to throng Malaysia by millions, and hence are considered as valuable resources that need to be preserved to ensure their sustainability. Equally valuable are the indigenous arts and handicrafts which are sold and traded by craft centres set by the government or by private sellers. Unfortunately, these arts and handicrafts have fallen prey to counterfeit and fakes. This paper examines national initiatives to regulate the sales of the indigenous people’s arts and crafts as a means of constraining the misappropriation of these cultural expressions in Malaysia, with comparison to Australia, New Zealand and the United States of America. This paper uses the mixed methods of library based and qualitative research. The latter consists of unstructured, face-to-face interviews with respondents from selected communities of aborigines in Peninsular Malaysia as well as Sabah and Sarawak. The focus is to explore and understand the problem and to observe whether misappropriation and dilution is of a real issue within the indigenous people. Based on the information and data collected from the interviews, the problem of misappropriation proves to be a real threat over the sanctity of indigenous people's cultural expression, in particular their arts and crafts. The paper concludes that Malaysia must adopt a multi prong approach including a range of laws to effectively curb the misappropriation of indigenous arts and crafts as well as preventing them from being diluted.